Development of E-Modules on Problem-Based Learning to Enhance Students Science Literacy - Asnidar, Asnidar; Safriana, Safriana; Jalil, Saifuddin Muhammad; Sakdiah, Halimatus; Zahara, Syarifah Rita (Universitas Syiah Kuala, 2024)
Interactive electronic modules are teaching materials used in the learning process with the help of today's technology which is useful for forming a more creative learning process. This development research method refers to Research and Development (RD) with the ADDIE model. The research subjects were 11th-grade Science 4, totalling 31 students and the research objects were located at Kejuruan Muda Public High School 1. Data collection instruments in the form of pretest and post-test and an interest questionnaire regarding the e-module. Data analysis is qualitative data analysis and quantitative data analysis. The results obtained are from material experts in the